Pengaruh Good Corporate Governance Dan Firm Size Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Ratih Kusuma Mawardani; Imam Baidlowi; Tatas Ridho Nugroho; Nur Ainiyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to examine the effect of independent variables on the dependent variable and examine moderating variables that can support the relationship between the independent variable and the dependent variable. The independent variables used in this study are Good Corporate Governance (GCG) and Firm size, and the dependent variable is firm value and the moderating variable used is profitability. The method used in this research is quantitative method. The population in this study was 59 Go Public companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used in this study was purposive sampling technique and obtained sample results of 13 companies during the 2019-2022 period with a total sample of 52 financial reports. Hypothesis testing in this study used Partial Least Square (PLS) analysis. The results showed that Good Corporate Governance (GCG) and firm size have a significant positive effect on firm value, while profitability has no significant effect in moderating the relationship between Good Corporate Governance (GCG) and firm size on firm value.